A beleza de dentro para fora: um estudo sobre motivações do consumo de dermocosméticos e autoestima com mulheres de diferentes gerações - Santos, Thayná Graciano dos (2023)
This study addresses Brazilian women’s consumption behavior in the dermocosmetics category. This research aimed to identify the influence of consumer motivations and selfesteem on the intention to purchase dermocosmetics by Brazilian female consumers of different generations. The theoretical review focused on hedonic and utilitarian, extrinsic and intrinsic motivations from the theory of self-determination and self-esteem in relation to dermocosmetic products. The literature review showed a smaller number of studies in the Brazilian context. A descriptive, quantitative empirical study was conducted through a survey of 432 Brazilian dermocosmetics consumers. Scales on hedonic motivation, utilitarian motivation, extrinsic motivation, intrinsic motivation, self-esteem, and purchase intention were used after being translated and adapted. The results showed that the greater the utilitarian motivation, the greater the purchase intention of dermocosmetics with significant levels for all generations. Also, results demonstrated that the greater the hedonic motivation, the lower the purchase intention of dermocosmetics for Generation Z. Another relevant result showed that the greater the extrinsic motivation, the lower the purchase intention for Generation Y. No significant statistical evidence was found, either in aggregate form or broken down by generation, that intrinsic motivation positively influences the purchase intention of dermocosmetics. Self-esteem, in general, influences the different types of motivation similarly across generations, its strongest influence being on hedonic motivation. As a theoretical contribution, three-dimensionality was identified in the existing self-esteem scales developed by Rosenberg (1965) and in Babin, Darden and Griffin’s (1994) utilitarian motivation scale. Also, we found evidence of bidimensionality in the purchase intention scale defined by Chandran and Morwitz (2005). As an empirical contribution, we highlight the discussion of diverse motivations and behaviors among female consumers from different generations.